Kepentingan pertumbuhan premis kitar semula dalam pengurusan sisa di Malaysia - Zaini Sakawi; Katiman Rostam; Abd Rahim Md Nor (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2008)
The rapid development of the Metropolitan City Region-Langat Klang Valley on the city edges give a lot of changes on the growth of settlements, socio-economic, transport and communication, and quality of physical environment. The changes occur not only have an impact on the population growth, use of space, social issues, the transfer of government departments, institutions, and upgrading of the economy, but the impact on the environment itself. In other words, the spill-over of the development has positive and negative impacts on changes in physical, social, economic and surrounding areas. This article will discuss the impact of changes in the development of the Metropolitan Region Town on the environmental changes, particularly increasing the growth of recycling premises in the vicinity of Kuala Langat District Council. The change has to be seen in terms of the number of premises used in recycling, types of materials purchased for recycling and participation in recycling operations. The study was conducted during the months from October to December 2007. The analysis is based on the amount of recycling premises registered under the district council. A checklist was used to identify the types of materials collected, recycling activities, and the factory product. The findings showed that the growth of recycling premises serve as a phenomenon that directly help to reduce the quantity of solid waste to landfills and economic generator for local residents and the premises of a recycling